AUTO DIAL SEBAGAI APLIKASI CALL DIVERT PADA TELEPON RUMAH - Santoso, Gatot (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
Demanding of telecommunication is a basic need as human being to have socia-lization in the neighborhood, and the function of the communication itself is to take and give information between someone to other, the information contains picture, voice, tex and video or combination among them. The way to design and build the auto dial as a call divert application on the phone home started from literature, then obtaining components and continued by designing hardware and software finally ended by trial the device. The device that is utilized to build auto dial as a call divert application on the phone home is a couple of walkie talkie, a te-lephone set, microcontroller and electronic components.